"Desirable models of behaviour" : learning to teach as a rite of passage : an historical study of initial teacher education in New Zealand : a dissertation presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Education at Massey University, Palmerston North, New Zealand - Ball, Teresa (Massey University, 2009)
This thesis critically examines the historical construction of initial teacher education at the turn of the 20th century. It focuses particularly on the extent of state involvement in the process of learning to teach, arguing that this process fulfils the necessary conditions of a rite of passage. The investigation utilises a different theoretical and methodological approach which combines the post-structuralist analyses of Michel Foucault with the cultural-anthropological work of Arnold van Gennep. Together, they provide a framework which enables an archaeological examination of teacher training at the macro-level of the state and its institutions, whilst providing a complementary, genealogical analysis of student teachers at the micro-level of their everyday lives. The investigation found that, in order to transform colonial society into an enlightened rural democracy, the state needed to transform its teachers. It did this through ensuring neophyte teachers passed through a carefully orchestrated rite of passage within a highly centralised and regulated system of training colleges. This necessitated a shift away from the devolved, differentiated pupil-teacher training system. The study traces this move, examines the state?s rationale, and explores the implications for all three phases of the trainees? rite of passage: separation, transition and incorporation. It also explains how specific „ceremonial rituals? and „sacred knowledge? prescribed what new teachers should know and do in order to become productive, docile and economically useful members of society. The study also emphasises that student teachers became subjects-in-their-own-making within this regime of order. The study then shifts its focus to the present, „re-meeting? history by comparing the ritual practices and specialist knowledge of past rites of passage with those of the present. It challenges teacher educators and teachers to take control of teacher education and suggests ways in which they should take advantage of its location in the university by opening up new political spaces and reasserting the importance of professionalism in action.
Keywords: Teacher education; Teacher training; New Zealand; Fields of Research::330000 Education::330300 Professional Development of Teachers